Experimental Study of Spring Harmonic Vibrations and Investigation of Changes, Spring Constant as a Function of Its Mass - Khawari, Rajab Ali (Journal of Natural Sciences – Kabul University, 2024)
Springs are widely used elastic systems in various fields and it is necessary to obtain the spring constant. The spring constant is a function of many variables that have been experimentally measured on the effect of spring mass on spring constant changes. The concept of effective mass and its value were investigated experimentally in the ranges where the mass of the foreign body is between 0.2-10 times the weight of the spring coil. From the graphical and numerical analysis, it can be seen that the experimental results are close to the theoretical result of 0.33 in a range of ≤M≤4 , but the outside of this interval, the experimental results are different from the theoretical value. Without taking into account the effect of gender as well as the effect of size and that the return property of the spring to the initial state is different for different springs, it can be understood due to the contradiction of the experimental answer with the theoretical answer in large intervals. Data collection in the physics laboratory was done with an optical timer by an accuracy of 0.001s, and a millimeter ruler, which the result as a linear graph of the period square to the mass function in all measurement intervals shows an intersection of 0.035, which gives a value of 0.384 for the mass coefficient of the spring.